Cyclic lipopeptides from Bacillus subtilis activate distinct patterns of defence responses in grapevine. (24th August 2014) - Farace, Giovanni; Fernandez, Olivier; Jacquens, Lucile; Coutte, François; Krier, François; Jacques, Philippe; Clément, Christophe; Barka, Essaid Ait; Jacquard, Cédric; Dorey, Stéphan
Summary Non‐self‐recognition of microorganisms partly relies on the perception of microbe‐associated molecular patterns (MAMPs) and leads to the activation of an innate immune response. Bacillus subtilis produces three main families of cyclic lipopeptides (LPs), namely surfactins, iturins and fengycins. Although LPs are involved in induced systemic resistance (ISR) activation, little is known about defence responses induced by these molecules and their involvement in local resistance to fungi. Here, we showed that purified surfactin, mycosubtilin (iturin family) and plipastatin (fengycin family) are perceived by grapevine plant cells. Although surfactin and mycosubtilin stimulated grapevine innate immune responses, they differentially activated early signalling pathways and defence gene expression. By contrast, plipastatin perception by grapevine cells only resulted in early signalling activation. Gene expression analysis suggested that mycosubtilin activated salicylic acid (SA) and jasmonic acid (JA) signalling pathways, whereas surfactin mainly induced an SA‐regulated response. Although mycosubtilin and plipastatin displayed direct antifungal activity, only surfactin and mycosubtilin treatments resulted in a local long‐lasting enhanced tolerance to the necrotrophic fungus Botrytis cinerea in grapevine leaves. Moreover, challenge with specific strains overproducing surfactin and mycosubtilin led to a slightly enhanced stimulation of the defence response compared with the LP‐non‐producing strain of B. subtilis. Altogether, our results provide the first comprehensive view of the involvement of LPs from B. subtilis in grapevine plant defence and local resistance against the necrotrophic pathogen Bo. cinerea. Moreover, this work is the first to highlight the ability of mycosubtilin to trigger an immune response in plants.